Evaluation of potential and biology of Spodoptera pectinicornis (Hampson) for the biological control of aquatic weed Pistia stratiotes - Nowshad, I.; Thiruchchelvan, N.; Mikunthan, G. (University of Jaffna, 2025)
Pistia is considered the most invasive aquatic monocot weed globally due to its high multiplication potential. The larvae of the phytophagous Spodoptera pectinicornis (Lepidoptera) were found to damage P. stratiotes extensively. Hence, this study aimed to investigate the biology and feeding potential of S. pectinicornis. Initially, aquatic weed Pistia was reared in a container with pond water, and the bioagent, S.pectinicornis, was inoculated on Pistia to study its life cycle. The life cycle of S. spectinicornis consists of four stages: egg, larvae, pupa, and adult. The mean diameter of an egg was 0.317 ± 0.020 mm. There were six larval instars in S. pectinicornis. The sex differentiation was observed in the 5th and 6th instars, and the testes' mean length and width were 1.187 ± 0.11 mm and 0.716 ± 0.085 mm, respectively. Sexual dimorphism was observed; male and female genital distances were 0.219 ±0.021 mm and 0.701 ± 0.058 mm, respectively. Adult males had pectinate antennae, whereas females had filiform antennae. The leaf damage by different instars of larval S. pectinicornis was 1st instar 0.017 cm2 (0.348%), 2nd instar 0.025 cm2 (0.528%), 3rd instar 1.50 cm2 (30.564%), 4th instar 2.634 cm2 (58.132 %), 5th instar 3.306 cm2 (67.342 %), 6th instar 4.482 cm2 (91.256%) in 12 hours. The larvae cause significant damage to the leaves, apical buds, and flowers of Pistia, with leaf damage reaching 91%, adversely affecting photosynthesis. Most feeding occurred during the later larval instars, which correlates with maximum damage. But it was observed that P. stratiotes reproduced through stolons, producing 8–9 young plants per colony, which were relatively unaffected by phytophagy, while seed production was compromised. Even though the rapid reproductive cycle of S. pectinicornis minimizes photosynthesis and seed production, developing a management strategy focused on controlling stolon multiplication is essential to mitigate the spread of P. stratiotes.
Keywords: Feeding Potential; Morphometrics; Pistia; Sexual dimorphism; Spodoptera pectinicornis